Francoist representations in the monetary issues of the reign of Juan Carlos I (1975-2014) (2021)
This paper contains a review of all the legal tender coins that display an iconography associated with the Franco dictatorship during the reign of Juan Carlos I of Spain (1975-2014), except for collectible coins (commemorative gold and silver pieces whose destination is not ordinary circulation, but the world of numismatic collecting). In the search for greater scientific independence, three different historical-political positions (conservative, moderate and progressive) were put forward about the cataloguing of these pieces. The results determined that the predominance of Francoist symbology in the 1970s gradually diminished, but if the king himself were to be considered a Francoist element, this iconography would be maintained during the entire historical period. © 2021 Ediciones Hecate. All rights reserved.